Closing Sexual Health Service Gaps With a New Service Model in Germany: Performance of an on-Site Integrated, Cross-Sectoral, Low Threshold Sexually Transmitted Infections/HIV Counseling and Treatment Service - Matthias C. Müller; Matthias C. Müller; Susanne Usadel; Stefan Zimmermann; Andreas Fahrhöfer; Winfried V. Kern; Ulrike Hoffmeister; Siegbert Rieg (Frontiers Media S.A., 2022)
PurposeIn Germany, the incidence of bacterial sexual transmitted infections (STI) is on the rise and still high for HIV infections. The Center for Sexual Health Freiburg (CSHF) was established to offer low threshold access for STI/HIV counseling, testing, HIV pre-exposure prophylaxis (PrEP), and on-site treatment. The objective of this study was to analyze the performance of CSHF.MethodsLongitudinal study that includes all clients presenting between 1 May 2020 and 28 February 2021 at CSHF and willing to sign informed consent.ResultsIn the study period, 536 clients presented at CSHF of whom 417 clients were included in the study resulting in 668 client contacts. Clients' median age was 28.1 years (range: 18.0-73.1), 55.9% were men, 42.0% were women, 0.3% were transman, and 1.7% were not binary. Clients' sexual orientation was heterosexual (56.6%), homosexual men (26.2%), and bisexual (13.6%). STI screening resulted in the detection of any STI in 3.4% (95% confidence interval (CI): 0.7-6.1) of women, in 3.1% (95% CI: 0.0-6.5) of heterosexual men, and in 22.2% (95% CI: 13.0-31.5) of men having sex with men (MSM) not taking PrEP. Eighty-one MSM received PrEP with a total follow-up of 57.3 person-years and 0.44 STIs per person-year.ConclusionThe substantial burden of STI in the study population emphasizes the need for regular and low threshold STI screening services. The concept of CSHF may facilitate access to STI/HIV counseling, testing, and PrEP for a wide spectrum of people and may prove to be an important contribution to the efforts to reduce STI and HIV incidence in Germany.